Exploring Energy Management on GPUs in Game Architectures - Marcelo Zamith; Luis Valente; Mark Joselli; José Ricardo Silva Junior; Esteban Clua; Bruno Feijó (Journal on Interactive Systems, 2014)
Nenhum resumo disponível